2016
DOI: 10.1177/1535370215622583
|View full text |Cite
|
Sign up to set email alerts
|

Effects of resveratrol and methoxyamine on the radiosensitivity of iododeoxyuridine in U87MG glioblastoma cell line

Abstract: The purpose of this study was to evaluate the combination effect of resveratrol and methoxyamine on radiosensitivity of iododeoxyuridine in spheroid culture of U87MG glioblastoma cell line using colony formation and alkaline comet assays. Spheroids on day-20 with 350 µm diameters were treated with 20 µM resveratrol and/or 6 mM methoxyamine and/or 1 µM iododeoxyuridine for one volume doubling time (67 h), and then irradiated with 2 Gy gamma-radiation ((60)Co) in different groups. After treatment, viability of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Furthermore, RSV extremely blocked HIF-1 a protein secretion by altering both protein translation as well as HIF1-α protein mortification (39). It is therefore confirmed that RSV to augmented the IUdR absorption in hypoxia cells (64).…”
Section: Effects Of Resveratrol On the Radiosensitivity Of Iododeoxyumentioning
confidence: 67%
See 4 more Smart Citations
“…Furthermore, RSV extremely blocked HIF-1 a protein secretion by altering both protein translation as well as HIF1-α protein mortification (39). It is therefore confirmed that RSV to augmented the IUdR absorption in hypoxia cells (64).…”
Section: Effects Of Resveratrol On the Radiosensitivity Of Iododeoxyumentioning
confidence: 67%
“…Iododeoxyuridine (IUdR) is halogenated pyrimidines analogues. It is one the most effective non-hypoxic radiation sensitizers (64,119). It is a thymidine analogue so it able to insert itself into DNA during the cell cycling.…”
Section: Effects Of Resveratrol On the Radiosensitivity Of Iododeoxyumentioning
confidence: 99%
See 3 more Smart Citations